182k views
2 votes
PLEASE HELP ME SOMEONE

PLEASE HELP ME SOMEONE-example-1
User Gimly
by
4.1k points

1 Answer

6 votes

Answer:

Option 2: 27 is the correct answer.

Explanation:

Given functions are:


f(x) = x^2-2\\g(x) = 4f(x) - 1

As we can see that the function g(x) in written in terms of f(x), first of all we have to find g(x) by putting the value of f(x) in g(x)

So putting f(x) = x^2-2 in g(x)


g(x) = 4(x^2-2)-1\\= 4x^2-8-1\\=4x^2-9

As g(-3) has to be found, putting x=-3 in g(x)


g(-3) = 4(-3)^2-9\\= 4(9)-9\\=36-9\\=27

Hence

Option 2: 27 is the correct answer.

User VBNight
by
4.4k points